Angle-Dependent Distortions in the Perceptual Topology of Acoustic Space. (May 2018) - Brimijoin, W. Owen
By moving sounds around the head and asking listeners to report which ones moved more, it was found that sound sources at the side of a listener must move at least twice as much as ones in front to be judged as moving the same amount. A relative expansion of space in the front and compression at the side has consequences for spatial perception of moving sounds by both static and moving listeners. An accompanying prediction that the apparent location of static sound sources ought to also be distorted agrees with previous work and suggests that this is a general perceptual phenomenon that is not limited to moving signals. A mathematical model that mimics the measured expansion of space can be used to successfully capture several previous findings in spatial auditory perception. The inverse of this function could be used alongside individualized head-related transfer functions and motion tracking to produce hyperstable virtual acoustic environments.